The Use of Youtube as a Digital Literacy Medium for SelfAwareness and Self-Management of Elementary School Students - Habib, Gilang Nur; Wulandari, Murfiah Dewi (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: This study investigates how YouTube use influences two key aspects of student self‐development—self‐awareness and self‐ management—among upper‐elementary learners, aiming to clarify whether YouTube, as a digital‐literacy medium, facilitates or hinders these psychological competencies. Methodology: A quantitative correlational design was employed with a randomly selected sample of 215 fourth‑ to sixth‑grade students from various elementary schools in Colomadu District, Karanganyar Regency. Data were collected via a 5‑point Likert–scale questionnaire, supplemented by classroom records and direct observations. Hypothesis testing involved independent‑samples t‑tests and simple linear regression analyses (using the unstandardized B coefficient) to assess the linear relationships between YouTube usage (independent variable) and each outcome—self‐awareness and self‐management (dependent variables). Results: Analysis revealed that YouTube use did not exert a statistically significant effect on students’ self‐awareness scores. In contrast, YouTube use showed a significant but negative relationship with self‐management (p < 0.05), indicating that higher levels of YouTube engagement were associated with lower self‐management competencies among the surveyed learners. Applications/Originality/Value: These findings contribute to digital‐literacy research by distinguishing YouTube’s differential impacts on distinct psychological skills. Educators and parents can use this insight to develop guided‐use protocols and targeted interventions— such as integrating self‐management training into digital‐media lessons—to mitigate negative effects. Future studies might build on this work by exploring which specific YouTube content or usage patterns most strongly predict self‐management deficits, thereby informing more nuanced policy and pedagogical recommendations.